Estrogen receptor alpha expression in fattening pig’s testes by the timing of the first injection for immunocastration - Srisuwatanasagul S. (2023)
The purpose of this study was to examine the expression of estrogen receptor alpha (ERα) in the testicular tissues of male fattening pigs injected with the first gonadotropin-releasing hormone (GnRH) vaccine (Improvac™, Zoetis, Thailand) for immunocastration 6 weeks earlier than the standard protocol. All pigs (n=24) were divided into three groups on the criterion of immunocastration protocol: A (n=8) was injected with GnRH vaccine at 15 and 19 weeks old, B (n=8) received GnRH vaccine at 9 and 19 weeks old, and C (n=8) remained untreated. Expression of ERα was investigated using an immunohistochemistry, appraised by an image analysis application (3DHISTECH, Budapest, Hungary), and reported as a H-score. The results revealed that testicular histoarchitecture of the immunocastrated pigs was less developed than that of the intact pigs. ERα was localized both in the seminiferous tubules and interstitial areas of all groups. ERα H-score of the C pigs was lowest (5.49±4.17) among groups and significantly lower than that of both A and B groups (P<0.05). However, the H-score of ERα between A and B groups was not different from each other (21.41±12.61 vs 23.91±11.47, P>0.05). In summary, the first injection of GnRH vaccine either at 9 or 15 weeks of age contributed to a similar result of testicular ERα expression.